A repetitive sampling plan using decision trees method. Issue 4 (18th May 2020) - Azam, Muhammad; Aslam, Muhammad; Niaki, Seyed Taghi Akhavan
Abstract: In this paper, a novel acceptance sampling strategy based on the decision trees approach is proposed to make decisions on either to accept or to reject a submitted lot. The strategy is constructed for the variable repetitive sampling plan using the process capability index. The new decision trees strategy makes decisions in a broader sense by selecting the most influential predictors along with the best splitting points from the values used in the past for inferring any decision on their class. The application of the proposed strategy along is demonstrated using some industrial examples.